Cheesecake Manor, Californie : Raymond Chandler entre roman à énigme et roman hard-boiled - Isabelle Boof-Vermesse (Transatlantica)
One of the founding fathers of American detective fiction, Raymond Chandler is also a theoretician of the genre. In his critical essays, "The Simple Art of Murder" (1944), "Casual Notes on the Mystery Novel" (1949), "Notes on English and American Style" (1949), "Introduction to Killer in the Rain" (1950), Chandler contrasts hard-boiled fiction with its British counterpart, the whodunit, to propose a definition by exclusion of the American formula. In a series of parodic variations on preterition, Chandler the essayist claims to demonstrate the vacuous ineptitude of the rival form, but in doing so he reveals inadvertently a secret longing of Chandler the novelist. The satirical impulse is directed against the American imitation of the British form rather than its original version, revealing Chandler’s strategy to avoid the dead end of imitation. Adopting a conspicuously American persona while inscribing himself within the decalogue tradition that sets up the rules of the whodunit as game, Raymond Chandler differentiates between the two formulas in an attempt to break away from a textual production marked as sub-literary. Ultimately, what is at stake in the essays is to establish hard-boiled fiction as canonic literature.